CRIMES AGAINST HONOR: LEGAL ABRACTIONS IN THE CRIMINAL SYSTEM AND ETHICAL DETURPTIONS - Fernandes Ferreira, Henrique Matheus (Revista Fronteiras Interdisciplinares do Direito, 2020)
This article will address the criminal tutelage and the classification of crimes against honor, in its social evolution of the concept of legal good within the theory of the crime, observing from the principle bases of Criminal Law under a perspective of Libertarian Ethics, as evidenced that verify a possible unconstitutionality of the offenses of injury, defamation and slander, as for presenting a facet of a legislative hypertrophy and a bankruptcy for a symbolic criminal law and, even, a criminal right of the enemy of third speed.